A longitudinal high‐risk study of adolescent anxiety, depression and parent‐severity on the developmental course of risk‐adjustment. (6th June 2014) - Rawal, Adhip; Riglin, Lucy; Ng‐Knight, Terry; Collishaw, Stephan; Thapar, Anita; Rice, Frances
<x xml:space="preserve">Abstract</x> Background Adolescence is associated with developments in the reward system and increased rates of emotional disorders. Familial risk for depression may be associated with disruptions in the reward system. However, it is unclear how symptoms of depression and anxiety influence the development of reward‐processing over adolescence and whether variation in the severity of parental depression is associated with hyposensitivity to reward in a high‐risk sample. Methods We focused on risk‐adjustment (adjusting decisions about reward according to the probability of obtaining reward) as this was hypothesized to improve over adolescence. In a one‐year longitudinal sample (N = 197) of adolescent offspring of depressed parents, we examined how symptoms of depression and anxiety (generalized anxiety and social anxiety) influenced the development of risk‐adjustment. We also examined how parental depression severity influenced adolescent risk‐adjustment. Results Risk‐adjustment improved over the course of the study indicating improved adjustment of reward‐seeking to shifting contingencies. Depressive symptoms were associated with decreases in risk‐adjustment over time while social anxiety symptoms were associated with increases in risk‐adjustment over time. Specifically, depression was associated with reductions in reward‐seeking at favourable reward probabilities only, whereas social anxiety (but not generalized anxiety) led to reductions in reward‐seeking at low reward probabilities only. Parent depression severity was associated with lowered risk‐adjustment in offspring and also influenced the longitudinal relationship between risk‐adjustment and offspring depression. Conclusions Anxiety and depression distinctly alter the pattern of longitudinal change in reward‐processing. Severity of parent depression was associated with alterations in adolescent offspring reward‐processing in a high‐risk sample.